2021
DOI: 10.21037/jtd-20-3108
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pulmonary nodules caused by nontuberculous mycobacteriosis in 101 resected cases: multi-center retrospective study

Abstract: Background: Solitary pulmonary nodules caused by nontuberculous mycobacteriosis are included as a category of pulmonary nontuberculous mycobacterium disease. Clinical characteristics, treatments and prognosis are not fully known because there are a few related reports. Methods: This was a multi-center retrospective study of 101 cases diagnosed as solitary nodular type of nontuberculous mycobacteriosis from January 2000 to March 2017 that underwent resection at 9 related facilities belonging to the Thoracic Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…As FDG collects in granulation tissues formed by activation of macrophages in NTM infection, the amount of FDG accumulation is positively associated with the scope of active inflammatory areas 89 . In a study by Del Giudice et al, FDG-PET/CT was found useful in revealing the activity and extent of disease by monitoring metabolic activity of various pulmonary lesions in NTM disease 90 .…”
Section: Nontuberculous Mycobacterial Infectionsmentioning
confidence: 99%
“…As FDG collects in granulation tissues formed by activation of macrophages in NTM infection, the amount of FDG accumulation is positively associated with the scope of active inflammatory areas 89 . In a study by Del Giudice et al, FDG-PET/CT was found useful in revealing the activity and extent of disease by monitoring metabolic activity of various pulmonary lesions in NTM disease 90 .…”
Section: Nontuberculous Mycobacterial Infectionsmentioning
confidence: 99%
“…The relevance of mycobacteriosis was raised after an increase in mortality of AIDS patients with generalised NTMB infection was noted (Ose et al, 2021;Thomas et al, 2023). The increase in the incidence of mycobacteriosis is associated with immunosuppression resulting from glucocorticoid and cytostatic therapy, treatment with tumour necrosis factor α blockers (Taira et al, 2018), a decrease in the spread of tuberculosis (Madzinga et al, 2022), and improved methods of isolation and identification of NTMB (Haworth et al, 2017;Kok et al, 2022).…”
Section: Introductionmentioning
confidence: 99%